Accounting for distress in bank mergers - Michael Koetter; Jaap W. B. Bos; Frank Heid; Clemens J. M. Kool; James W. Kolari; Daniel Porath (Deutsche Bundesbank, 2005)
The inability of most bank merger studies to control for hidden bailouts may lead to biased results. In this study, we employ a unique data set of approximately 1,000 mergers to analyze the determinants of bank mergers. We use data on the regulatory intervention history to distinguish between distressed and non-distressed mergers. We find that, among merging banks, distressed banks had the worst profiles and acquirers perform somewhat better than targets. However, both distressed and non-distressed mergers have worse CAMEL profiles than our control group. In fact, non-distressed mergers may be motivated by the desire to forestall serious future financial distress and prevent regulatory intervention.
Keywords: G21; G14; G34; 330; Mergers; bailout; X-efficiency; multinomial logit; Bank; Fusion; Übernahme; Unternehmenssanierung; Bankinsolvenz; Schätzung; Deutschland